1996
DOI: 10.2527/1996.741218x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled, reversible suppression of estrous cycles in beef heifers and cows using agonists of gonadotropin-releasing hormone.

Abstract: Agonists of GnRH were examined for their potential to achieve controlled, reversible suppression of estrous cycles in beef cattle. In Exp. 1, cyclic heifers received two (Group B2) or four (Group B4) buserelin (D-Ser[Bu(t)]6-Pro9-LHRH[1-9] nonapeptide ethylamide) implants and degree of cessation of estrous cycles was monitored. Treatment with buserelin caused estrous cycles to cease, as indicated by basal (.2 ng/mL) concentrations of progesterone, for 48.4 +/- 3.8 d (mean +/- SEM) in Group B2, which was less (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…The process of down-regulation has been described previously in other species and is initiated by long-term exposure to GnRH agonist. This effect causes a reduction in GnRH receptors on gonadotropes (Clayton, 1989), depletion of pituitary LH and follicle-stimulating hormone content (Aspden et al, 1996), and elimination of the preovulatory LH surge (Gong et al, 1995;D'Occhio et al, 1996). These responses have been shown to result in ovulation failure and infertility, which persists as long as the agonist is present in circulation at therapeutic levels (Melson et al, 1986;D'Occhio et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The process of down-regulation has been described previously in other species and is initiated by long-term exposure to GnRH agonist. This effect causes a reduction in GnRH receptors on gonadotropes (Clayton, 1989), depletion of pituitary LH and follicle-stimulating hormone content (Aspden et al, 1996), and elimination of the preovulatory LH surge (Gong et al, 1995;D'Occhio et al, 1996). These responses have been shown to result in ovulation failure and infertility, which persists as long as the agonist is present in circulation at therapeutic levels (Melson et al, 1986;D'Occhio et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This effect causes a reduction in GnRH receptors on gonadotropes (Clayton, 1989), depletion of pituitary LH and follicle-stimulating hormone content (Aspden et al, 1996), and elimination of the preovulatory LH surge (Gong et al, 1995;D'Occhio et al, 1996). These responses have been shown to result in ovulation failure and infertility, which persists as long as the agonist is present in circulation at therapeutic levels (Melson et al, 1986;D'Occhio et al, 2000). Our findings are consistent with previous observations of acute and chronic responses reported in sheep (Dobson, 1985), cattle (D 'Occhio et al, 1989;Gong et al, 1996), horses (Montovan et al, 1990), deer (Becker andKatz, 1995), and elk (Baker et al, 2002) treated with GnRH agonist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous observations and other studies [7,30] showed that ovarian P4 production could be prevented by strategic use of a GnRH-agonist to create progesterone-free animals similar to ovarietomised cows. In order to block endogenous production of P4, each cow initially received a 6 mg Deslorelin (GnRH-agonist; D-Trp 6 -D-Trp 6 -Pro 9 -des-Gly 10 -GnRH ethylamide) ear implant (Peptech Animal Health, Sydney, Australia) initially, followed by two injections of prostaglandin F2α (2 mL Prosolvin, Intervet, Melbourne) at 0800 and 1600 h, 10 days later (Fig.…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%